SWOT Analysis in a Disruptive 5.0 Society on Human Resources Management - Mohammad Syarief Nur Maulana (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
Human resource management is now faced with the disruptive society 5.0, which is closely related to human resource performance and which in the long run is correlated with economic growth. The purpose of this study is to investigate whether or not the SWOT analysis tool is useful for generating suggestions for different approaches to human resource management. In this study, descriptive and qualitative research techniques were used to analyze the social conditions necessary for human survival. This research teaches us that the WT Strategy, which consists of defending human resource management against errors and risks, is the most important strategy to implement. We obtained this information through reading studies. Research needs to be carried out in various disciplines to determine what the nation needs to fulfill the vision and capabilities of 5.0.